Tertampiknya Injil-injil Gnostik - Mika Sulistiono (Predica Verbum: Jurnal Teologi dan Misi, 2021)
Until now, challenges on the validity of the Bible based on the use of the Gnostic Gospels are still rampant, especially by anti-orthodox Christians and liberals. For this reason, this study attempts to answer the question of how the historical description of the Gnostic Gospels was dismissed in the century of its appearance, so that it did not enter the New Testament canon. Through a qualitative-descriptive research method, it was found that the answer to the rejection of the Gnostic Gospels as part of the canon was due to: 1). there is a significant time gap between the appearance of the Gnostic Gospels and the canonical ones, 2). its distribution was secret, and was not common among the early Christian congregations. 3). his teachings that contradict the teachings of the canonical gospels about the life of the Lord Jesus and the way of human salvation, 4). several important figures of the second to third centuries such as Irenaeus, Tertullian, Clemens, Origens, and Esuibius firmly rejected the Gnostic Gospels to enter the canon. The result of this research certainly confirms the Christian belief in the acknowledgment of the validity of the New Testament canon.